AN OVERVIEW OF USING COLLABORATIVE WRITING METHOD TO INCREASE STUDENTS’ WRITING ABILITY - Rosdiana (Getsempena English Education Journal, 2015)
This study reviews the effectiveness of using collaborative writing method to enhance students’ writing ability. It also tries to expand the scope of collaboration in all aspects of the EFL College writing process. First of all, this article explains the operational definition of collaborative learning process based on EFL writing instruction. In what follows, the article headlights the benefits of collaborative writing process in the EFL classroom. The remaining phase of this article discusses the steps and procedures in practicing writing based on collaborative process in the classroom. Anchored in this collaborative process based writing framework, a teacher enables students to engage in collaborative and dialogic activities through the process of writing. The definite aim is to help EFL college students in writing academic pieces better and more easily as they go through the writing process from pre- writing to post-writing.